Effects of Stigma and Discrimination Reduction Programs Conducted Under the California Mental Health Services Authority An Evaluation of Runyon Saltzman Einhorn, Inc., Documentary Screening Events - Cerully, Jennifer L. (RAND Corporation, 2015)
Describes the methods and results of a RAND evaluation of stigma and discrimination reduction efforts by Runyon Saltzman Einhorn, Inc., involving screenings of a documentary film called "A New State of Mind: Ending the Stigma of Mental Illness."